Turbulent Exchange Tensor in the Atmospheric Boundary Layer: An Inverse-Problem Approach Using Radiosonde Wind Observations with High Vertical Resolution - Vladimir A. Gordin; Dmitry S. Efremenko (Boundary-Layer Meteorology, 2026)

First total ozone column observations from the Ozone Monitoring Suite-Nadir (OMS-N) onboard China’s FengYun-3F satellite - Jian Xu; Yapeng Wang; Lin Chen; Dmitry Efremenko; Lanlan Rao; Gegen Tana; Shuanghui Liu; Qian Wang; Jinghua Mao; Yongmei Wang; Ling Sun; Huanhuan Yan; et al. (Science China Earth Sciences, 2025)

Distribution of rare earth elements and yttrium in water, suspended matter and bottom sediments in Lake Onego: Evidence of the watershed transformation in the Late Pleistocene - Vera Strakhovenko; Natalia Belkina; Dmitry Subetto; Alexander Rybalko; Natalia Efremenko; Natalia Kulik; Maxim Potakhin; Mikhail Zobkov; Ekaterina Ovdina; Anna Ludikova (Quaternary International, 2023)

Analysis of the Discrete Theory of Radiative Transfer in the Coupled “Ocean–Atmosphere” System: Current Status, Problems and Development Prospects - Viktor P. Afanas’ev; Alexander Yu. Basov; Vladimir P. Budak; Dmitry S. Efremenko; Alexander A. Kokhanovsky (Journal of Marine Science and Engineering, 2020)
In this paper, we analyze the current state of the discrete theory of radiative transfer. One-dimensional, three-dimensional and stochastic radiative transfer models are considered. It is shown that the discrete theory provides a unique solution to the one-dimensional radiative transfer equation. All approximate solution techniques based on the discrete ordinate formalism can be derived based on the synthetic iterations, the small-angle approximation, and the matrix operator method. The possible directions for the perspective development of radiative transfer are outlined.

Volcanic SO 2 plume height retrieval from UV sensors using a full-physics inverse learning machine algorithm - Dmitry S. Efremenko; Diego G. Loyola R.; Pascal Hedelt; Robert J. D. Spurr (International Journal of Remote Sensing, 2017)